Is Global Sisterhood Elusive? A Critical Assessment of the Transnational Women's Rights Movement - Tungohan, Ethel (Atlantis)

(untitled) (Mount Saint Vincent University, 2010)
The United Nations (UN) women's rights movement has historically ignored differences among women by promoting notions of a unified global sisterhood. In order to rectify the exclusions wrought by equality and difference feminism, intersectional analysis that takes account of group and economic rights becomes crucial. Only then can women's rights be universal.